2012
DOI: 10.1002/anie.201203284
|View full text |Cite
|
Sign up to set email alerts
|

Discotic Ionic Liquid Crystals of Triphenylene as Dispersants for Orienting Single‐Walled Carbon Nanotubes

Abstract: Orient and conduct: Triphenylene-based discotic ionic liquid crystals (ILCs) with six imidazolium ion pendants can disperse pristine single-walled carbon nanotubes (SWNTs). When the ILC is columnarly assembled, doping with SWNTs results in macroscopic homeotropic columnar orientation. Combination of shear and annealing treatments gives rise to three different orientation states, which determine the anisotropy of electrical conduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(40 citation statements)
references
References 35 publications
1
39
0
Order By: Relevance
“…[13] Two common approaches applied to this dispersion problem include covalent modification of SWCNT surfaces and noncovalent adsorption of functional small molecules and polymers. [14] Noncovalent modification of SWCNTs is particularly attractive because the strategy preserves the intrinsic properties of SWCNTs without disruption to the electronic and optical responses of the system. [15] It has been demonstrated that SWCNTs interact with conjugated species, such as pyrene derivates, [16] phthalocyanines, [17] porphyrins, [18] phenazine, [19] and thionine types of dyes, [20] based on π-π stacking.…”
mentioning
confidence: 99%
“…[13] Two common approaches applied to this dispersion problem include covalent modification of SWCNT surfaces and noncovalent adsorption of functional small molecules and polymers. [14] Noncovalent modification of SWCNTs is particularly attractive because the strategy preserves the intrinsic properties of SWCNTs without disruption to the electronic and optical responses of the system. [15] It has been demonstrated that SWCNTs interact with conjugated species, such as pyrene derivates, [16] phthalocyanines, [17] porphyrins, [18] phenazine, [19] and thionine types of dyes, [20] based on π-π stacking.…”
mentioning
confidence: 99%
“…Moreover, CNTs mixed with ILC containing ionized groups, which have excellent orientation, resulted in a highly efficient dispersion which is 1000 folds compared to the case of absence of ILC. This is attributed to the abundance of π‐electrons on CNTs surfaces which have great affinity for the positively charged ILC . This compact conducting surface of (CNTs ‐ ILC) with large surface area available for the reaction was more suitable for the assembly of crown ethers than CNTs.…”
Section: Resultsmentioning
confidence: 99%
“…ILCs possess the properties of ILs namely high ionic conductivity, chemical and thermal stability and intrinsic catalytic ability and that of liquid crystals . Also, the abundance of negative π‐electrons on CNTs surfaces had a great affinity for the positively charged ILCs . In previous work, we demonstrated that different ionic liquid crystals can be used as excellent active modifiers in the determination of several organic compounds .…”
Section: Introductionmentioning
confidence: 99%
“…Examples of applications of ILCs are anisotropic tribology [ 146 ] and ion conductivity to be used in molecular electronics (solar cells, optoelectronic devices, etc .) [ 35 , 37 , 38 , 147 , 148 ], in directed synthesis approaches [ 149 ], including controlled nanoparticle synthesis, [ 150 , 151 ], alignment [ 152 ] or deposition [ 153 ], in ionic self-assembly [ 154 , 155 ] that builds complex structures from simple charged organic species and possibly in bio-catalysis [ 156 ] or sensing applications [ 25 , 98 ]. The near future will demonstrate which roles ILCs can play.…”
Section: Discussionmentioning
confidence: 99%